Crystallization of sodium sulfate in porous media by drying at a constant temperature. (April 2015) - Saidov, T.A.; Pel, L.; van der Heijden, G.H.A.
Abstract: Sodium sulfate is generally seen as one of the most destructive salts in the weathering of historical objects. The crystallization which causes the damage can either be induced by drying and/or cooling of a salt solution in a porous material. In this study we have studied the crystallization of sodium sulfate during the drying of various porous materials at different temperatures. The experiments were conducted such that the Peclet number was smaller than one, i.e., the ion transport in the porous material is dominated by diffusion. The results show that at temperatures above 22 °C during the drying the anhydrous crystal phase of sodium sulfate, i.e., thenardite is eventually formed. Below 22 °C heptahydrate crystal phase is formed, which is metastable with respect to the corresponding mirabilite solubility.